2020
DOI: 10.1093/nsr/nwaa289
|View full text |Cite
|
Sign up to set email alerts
|

Operando surface science methodology reveals surface effect in charge storage electrodes

Abstract: Surface and interface play critical roles in energy storage devices, calling for operando characterization techniques to probe the electrified surfaces/interfaces. In this work, surface science methodology including electron spectroscopy and scanning probe microscopy has been successfully applied to visualize electrochemical processes at operating electrode surfaces in an Al/graphite model battery. Intercalation of anions together with cations is directly observed in surface region of the graphite electrode wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, PG presented an elevated volumetric change upon cycling. Wang et al recently observed the direct diffusion process of the intercalated ions underneath the highly ordered pyrolytic graphite (HOPG) surface by real-time optical microscopy, confirming more than 5-fold volume expansion by in situ atomic force microscopy (AFM) analysis …”
Section: Advanced Technologies For Characterizations and Simulationmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, PG presented an elevated volumetric change upon cycling. Wang et al recently observed the direct diffusion process of the intercalated ions underneath the highly ordered pyrolytic graphite (HOPG) surface by real-time optical microscopy, confirming more than 5-fold volume expansion by in situ atomic force microscopy (AFM) analysis …”
Section: Advanced Technologies For Characterizations and Simulationmentioning
confidence: 89%
“…Wang et al recently observed the direct diffusion process of the intercalated ions underneath the highly ordered pyrolytic graphite (HOPG) surface by real-time optical microscopy, confirming more than 5-fold volume expansion by in situ atomic force microscopy (AFM) analysis. 246 Song's group recently observed the thickness change of CoB/ few-layer graphene (FLG) composite positive electrodes during cycling by in situ SEM technology, which would provide an effective strategy for addressing the unexpected volume expansion, as shown in Figure 17. 110 It was observed that FLG presented huge volume expansion (50%) during charge and discharge, while the expansion of CoB and composite positive electrode was 5% and 10%, respectively.…”
Section: In Situ Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Operando XPS has been performed upon charging the planar model battery in an ultrahigh vacuum (UHV) XPS chamber (Figure S14), and the intensities of XPS Al 2p, Cl 2p, and N 1s signals increase but that of C 1s decreases (Figure S15). The binding energies (BEs) of the intercalants are all ∼1.7 eV lower than the surface absorption species due to the change in the surface work function …”
Section: Resultsmentioning
confidence: 99%
“…33,34 Considering the significant role of the atmosphere in ESDs, it is important to investigate atmosphere-dependent battery behaviors through operando/in situ characterization methodology. In this work, as exemplified by planar model aluminum ion battery (AIB) devices, 35,36 atmosphere-dependent relaxation and failure processes of the devices have been comprehensively studied by in situ Raman, XRD and X-ray photoelectron spectroscopy (XPS) within corresponding atmosphere-controlled characterization cells. In anhydrous atmospheres, the relaxation effects of the working graphite intercalation compound (GIC) electrodes are manifested by the GIC stage-structure change as well as electronic relaxation caused by ion redistribution.…”
Section: ■ Introductionmentioning
confidence: 99%